COMPARISON OF PRODUCTIVITY AND INCOME BETWEEN CASSAVA FARMERS USING AND NOT USING DOUBLE-ROW CULTIVATION TECHNOLOGY IN SUKADANA DISTRICT, LAMPUNG TIMUR REGENCY - Perdana, Aricha Dian; Haryono, Dwi; Lestari, Dyah Aring Hepiana (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2025)
The objective of this research is to examine the differences variations in cassava productivity between farmers who adopted the technology of double-row cultivation and those who did not, as well as the income derived from cassava farming in Sukadana District. This study was carried out in Muara Jaya Village, Sukadana District, East Lampung Regency, using a survey approach as the village is the sole place where the technology of double-row cultivation has been implemented for the first time. Among the samples, 21 farmers were adopted whereas 58 were not.  The analytical tool used to answer the first aim of the analysis was the calculation of Revenue/Cost (R/C), and the different tests. According to the findings, farmers who implemented the technology of double-row cultivation are able to grow cassava with 16.56 percent higher production. The income from cassava farming obtained by farmers who adopted the technology of double-row cultivation is 16.25 percent higher than those who did not adopt the technology of double-row cultivation. Keywords: cassava, double-row, production, revenue